2009
DOI: 10.1002/rcm.4302
|View full text |Cite
|
Sign up to set email alerts
|

Electrospray ionization mass spectrometry studies of cyclodextrin‐carboxylate ion inclusion complexes

Abstract: Aqueous solutions containing simple model aliphatic and alicyclic carboxylic acids (surrogates 1-4) were studied using negative ion electrospray mass spectrometry (ESI-MS) in the presence and absence of alpha-, beta-, and gamma-cyclodextrin. Molecular ions were detected corresponding to the parent carboxylic acids and complexed forms of the carboxylic acids; the latter corresponding to non-covalent inclusion complexes formed between carboxylic acid and cyclodextrin compounds (e.g., beta-CD, alpha-CD, and gamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 46 publications
0
19
0
Order By: Relevance
“…The role of the porogen was further tested using a CL-CDI (1:3) (cellobiose:CDI (1:3)) copolymer. CL is amphiphilic in nature due to its concave shape and may form complexes with apolar organic molecules, as concluded previously [39]. The isotherm generated from the sorption of PNP with CL-CDI (1:3) is shown in Fig.…”
Section: Sorption Of Pnpmentioning
confidence: 91%
See 2 more Smart Citations
“…The role of the porogen was further tested using a CL-CDI (1:3) (cellobiose:CDI (1:3)) copolymer. CL is amphiphilic in nature due to its concave shape and may form complexes with apolar organic molecules, as concluded previously [39]. The isotherm generated from the sorption of PNP with CL-CDI (1:3) is shown in Fig.…”
Section: Sorption Of Pnpmentioning
confidence: 91%
“…The equilibrium concentrations of NAs were determined using negative ion electrospray ionization mass spectrometry (ESI-MS). The instrumental conditions for the analyses of NAs have been described previously [39].…”
Section: Sorption Of Nasmentioning
confidence: 99%
See 1 more Smart Citation
“…In a follow-up study, Mohamed et al (9) reported the occurrence of molecular selectivity among congeners of NAs in aqueous solutions containing CDs, based on low-resolution mass spectrometry. The observed change in relative concentrations of oil sands acids is evident in Figure 3 by a comparison of the extract of NAs before and after equilibration with CD.…”
mentioning
confidence: 98%
“…The expanded definition includes oil sands acid-extractable organics with aromatic functional groups, nitrogen and sulfur atoms, along with unsaturated groups (15,16). For example, oil sands acids are known to fluoresce and evidently contain unsaturated and aromatic functionality that can be exploited using synchronous fluorescence spectroscopy and UV detection (9). OSPW contains thousands of oil Brought to you by | Western University Authenticated Download Date | 6/9/15 8:16 PM sands acids, many of which are only resolved using ultrahigh-resolution mass spectrometry.…”
mentioning
confidence: 99%